Influence of molybdenum doping on the structural, optical and electronic properties of WO3 for improved solar water splitting - Kalanur, Shankara S.; Seo, Hyungtak (Journal of Colloid and Interface Science, 2018)
Doping WO3 with foreign atoms is a very efficient strategy to modify the structural, optical and electronic properties which could influence its photoelectrochemical (PEC) water splitting activity. In this study, we report a simple and efficient single-step strategy for the fabrication of molybdenum (Mo)-doped WO3 thin films. The characterization results show that doping Mo into WO3 leads to a significant change in the morphology without changing its crystal structure. Elemental mapping and EDS analysis revealed that Mo was homogeneously doped into the crystal lattice of WO3 in the at.% range of 0–10.31. The incorporation of Mo into WO3 reduced the band-gap of WO3 and increased its light absorption ability. Notably, X-ray photoelectron spectroscopic valence band-edge analysis confirmed that substitution of Mo into WO3 led to a downward shift in the conduction band minimum without any significant change in the valence band maximum with respect to Fermi level. The fabricated Mo-doped WO3 electrodes exhibited a higher photocurrent compared to undoped WO3 samples under simulated 1.5 AM sunlight without the addition of a water oxidation catalyst. The procedure proposed herein provides a simple and systematic approach for the fabrication of band-gap-tailored WO3 photoanodes by Mo doping for efficient PEC water splitting.
Keywords: Band edge; Electrical conductivity; Incident photon-to-current efficiencies; Molybdenum doping; Photoelectrochemical water splitting; Tungsten oxide; Band-edge; Band-gap; Electrical conductivity; Impedance; Incident photon to current efficiency; Molybdenum doping; Morphology; Photocurrent; Photoelectrochemical water splitting; Tungsten oxide